2019
DOI: 10.1002/ppsc.201900224
|View full text |Cite
|
Sign up to set email alerts
|

Lock‐In Thermography to Analyze Plasmonic Nanoparticle Dispersions

Abstract: The physicochemical properties of nanoparticles (NPs) strongly rely on their colloidal stability, and any given dispersion can display remarkably different features, depending on whether it contains single particles or clusters. Thus, developing efficient experimental methods that are able to provide accurate and reproducible measures of the NP properties is a considerable challenge for both research and industrial development. By analyzing different NPs, through size and concentration, it is demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…LIT is a sensitive infrared imaging technique, which measures the thermal energy generated by plasmonic NPs upon excitation with light of specific wavelengths and is able to detect AgNPs in complex environments. 25,26 As reported in the literature, AgNP dissolution causes the overall absorbance to gradually reduce, 1 hence by irradiating AgNPs at their plasmon resonance, dissolution can be tracked by changes in the generated heat.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…LIT is a sensitive infrared imaging technique, which measures the thermal energy generated by plasmonic NPs upon excitation with light of specific wavelengths and is able to detect AgNPs in complex environments. 25,26 As reported in the literature, AgNP dissolution causes the overall absorbance to gradually reduce, 1 hence by irradiating AgNPs at their plasmon resonance, dissolution can be tracked by changes in the generated heat.…”
Section: Introductionmentioning
confidence: 91%
“…To analyse AgNP dissolution, LIT measurements were performed using a custom-made setup operating as reported previously. 26 Briefly, a multi-wavelength LED-based light source (AN178_2 61 LED module, ADOM, Germany) was used to stimulate the AgNPs at specific wavelengths and an infrared camera and is capable of capturing full-frame images at a rate of up to 200 Hz. A camera-link frame grabber transfers the acquired infrared images to a computer where they are processed in real time by a customdeveloped LabVIEW software according to the digital lock-in principle.…”
Section: Lock-in Thermography (Lit)mentioning
confidence: 99%
“…As previously reported, a custommade experimental setup, consisting of a homogeneous LEDbased light source which emits excitation light at various wavelengths; 400 nm, 525 nm and 730 nm (AN178 2 61 LED module, ADOM); an infrared camera (Onca-MWIR-InSb-320, XenICs, Belgium) mounted on a standard microscope stand (Leica Microsystems, Germany) and a personal computer as a processing unit was used to carry out the measurements. 21,22,24 Homogeneous spatial illumination of the sample was ensured by placing a light homogenizing glass rod (N-BK7, Edmond Optics, USA) between the LED panel and the sample. All samples were loaded into custom-made, spherical and light transparent sample holders.…”
Section: Lock-in Thermography (Lit)mentioning
confidence: 99%
“…20,21 In a recent study, the applicability of LIT for plasmonic NPs has been demonstrated, highlighting how NP aggregation can be resolved by changing the excitation wavelength. 22 LIT is based on exposing the sample to a periodic amplitude-modulated stimulation, while continuously imaging with an infrared (IR) camera to monitor the sample surface temperature over time. Instead of monitoring the change in temperature over time, the amplitude of the temperature oscillations (i.e., between on and off states of the external stimulus) is determined, thus enabling the selective filtering of background noise that is not originating from the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In LIT, the signal-to-noise ratio is significantly improved compared to other active thermal imaging techniques due to the averaging properties of the method and its ability to reject slowly varying thermal artifacts coming from the environment [ 23 ]. If an experiment can be mathematically modeled, LIT has the ability to deliver quantitative and semi-quantitative information on the NP heating slope [ 20 , 21 , 22 , 24 ]. The method is capable of resolving temperature differences, originating from magnetic NPs, which differ only slightly in size or shape and is highly sensitive to NP concentration.…”
Section: Introductionmentioning
confidence: 99%